IMPROVING TEACHER PERFORMANCE BASED ON CREATIVE MODEL - Alfiatur Rohmaniyah; Tatiek Nurhayati (UNISSULA, 2017)
This aims of the study is to describe and analyze the relationship between the effect of teacher creativity on teacher performance by work it self, innovative behavior and professional competence as an intervening variable. Based on the distribution of questionnaires to all Madrasah teachers in EastSemarang who were certified by 97, the sample of 88 respondents was obtained. The analytical tool in this researche is path analysis, where already validated and pass the reliability and classical assumptions were tested. The test results show that teacher creativity has a positive impact on work it self, innovative behavior and professional competence. The direct test results also show teacher creativity, work it self, innovative behavior and professional competence have a significant positive impact on the teacher performance. Work it self and innovative behavior also capable of being an intervening variable between teacher creativity and teacher performance. Professional competence is capable to be an intervening variable between teacher creativity and teacher performance, meaning that the higher theteacher’s ability to produce new ideas in the teaching and learning process, the competence or professionalism skills of teachers will increase so that it has an impact on the teacher performance achievement maximally.Keywords : teacher creativity, work it self, innovative behavior, professional competence and teacher performance.